The Long-Run Impact of Childhood Poverty and the Mediating Role of Education - Luna Bellani; Michela Bia (Institute of Labor Economics (IZA), 2017)
This paper examines the role of education as causal channel through which growing up poor affects the economic outcomes in adulthood in the European Union. We apply a potential outcomes approach to quantify those impacts and we provide a sensitivity analysis on possible unobserved confounders, such as child ability. Our estimates indicate that being poor in childhood significantly decreases the level of income in adulthood and increases the average probability of being poor. Moreover, our results reveal a significant role of education in this intergenerational transmission. These results are particularly relevant for Mediterranean and Central and Easter European Countries.
Keywords: D31; I32; I24; J62; 330; poverty; intergenerational transmission; potential outcome; causal mediation analysis; education